2015
DOI: 10.1093/ntr/ntu260
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Time Perception During Smoking Abstinence

Abstract: Introduction: Nicotine withdrawal leads to impulsive decision-making, which reflects a preference for smaller, immediate rewards and often prompts a relapse to smoking. The mechanism by which nicotine withdrawal leads to impulsive decision-making is not well known. An essential dimension of decision-making is time perception. Impulsive decisions reflect intolerance of temporal delays and the perception that time is passing more slowly. Sex may be an important factor in impulsive decision-making and time percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
2
13
1
Order By: Relevance
“…The significant abstinence effects on the TRT were in the predicted direction and are consistent with our previous study. 21 Moreover, this finding corresponded to a medium-sized effect (d = 0.43), similar to a previous study of time perception during abstinence. 40 The fact that abstinence significantly affected time reproduction, but had no effect on discounting, combined with the result that withdrawal-related changes in delay discounting, but not time reproduction or time discrimination, was predictive of shortterm cessation indicates that time perception and decision making may not be related psychological processes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The significant abstinence effects on the TRT were in the predicted direction and are consistent with our previous study. 21 Moreover, this finding corresponded to a medium-sized effect (d = 0.43), similar to a previous study of time perception during abstinence. 40 The fact that abstinence significantly affected time reproduction, but had no effect on discounting, combined with the result that withdrawal-related changes in delay discounting, but not time reproduction or time discrimination, was predictive of shortterm cessation indicates that time perception and decision making may not be related psychological processes.…”
Section: Discussionsupporting
confidence: 89%
“…37,38 Convergent evidence suggests that time perception may also account for the association between nicotine withdrawal and impulsive decision making. Preliminary evidence from our lab 21 and other labs 39,40 suggests that, during acute abstinence, smokers overestimate time. However, no study that we know of has examined whether changes in time perception were related to the ability to quit smoking.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Twenty‐three studies reported baseline exhaled CO levels, which had a weighted average of 25.1 parts per million (p.p.m.). The following tasks were reported by three or more studies, and therefore meta‐analysed: delay discounting , response inhibition , mental arithmetic , recognition memory , Stroop , smoking Stroop and dot probe tasks . As the number of studies in each analysis was relatively small ( k = 3–6), we did not explore study‐level moderators.…”
Section: Resultsmentioning
confidence: 99%
“…3.4 Time estimation task (Shah et al, 2016). Performance on the heartbeat tracking task might be confounded by one's ability to judge the duration of time intervals, and some evidence suggests that smokers may have poorer time estimation abilities than non-smokers, particularly during periods of abstinence (Ashare & Kable, 2015;Klein, Corwin & Stine, 2002;Sayette, Loewenstein, Kirchner & Travis, 2005). We controlled for this by asking half of the participants (randomly selected) in both conditions (n = 50) to complete a time estimation task.…”
Section: Participantsmentioning
confidence: 99%